Immune Regulatory Cell Bias Following Alemtuzumab Treatment in Relapsing-Remitting Multiple Sclerosis - Kashani, Nicole; Kelland, Eve E.; Vajdi, Borna; Anderson, Lauren M.; Gilmore, Wendy; Lund, Brett T. (Frontiers in Immunology, 2021)
Alemtuzumab is a highly effective treatment for relapsing-remitting multiple sclerosis. It selectively targets the CD52 antigen to induce profound lymphocyte depletion, followed by recovery of T and B cells with regulatory phenotypes. We previously showed that regulatory T cell function is restored with cellular repletion, but little is known about the functional capacity of regulatory B-cells and peripheral blood monocytes during the repletion phase. In this study (ClinicalTrials.gov ID# NCT03647722) we simultaneously analyzed the change in composition and function of both regulatory lymphocyte populations and distinct monocyte subsets in cross-sectional cohorts of MS patients prior to or 6, 12, 18, 24 or 36 months after their first course of alemtuzumab treatment. We found that the absolute number and percentage of cells with a regulatory B cell phenotype were significantly higher after treatment and were positivity correlated with regulatory T cells. In addition, B cells from treated patients secreted higher levels of IL-10 and BDNF, and inhibited the proliferation of autologous CD4+CD25- T cell targets. Though there was little change in monocytes populations overall, following the second annual course of treatment, CD14+ monocytes had a significantly increased anti-inflammatory bias in cytokine secretion patterns. These results confirmed that the immune system in alemtuzumab-treated patients is altered in favor of a regulatory milieu that involves expansion and increased functionality of multiple regulatory populations including B cells, T cells and monocytes. Here, we showed for the first time that functionally competent regulatory B cells re-appear with similar kinetics to that of regulatory T-cells, whereas the change in anti-inflammatory bias of monocytes does not occur until after the second treatment course. These findings justify future studies of all regulatory cell types following alemtuzumab treatment to reveal further insights into mechanisms of drug action, and to identify key immunological predictors of durable clinical efficacy in alemtuzumab-treated patients.